Spirituality, workplace spirituality and ethical mindsets: an Australian perspective - Issa, Theodora; Pick, David (Nova Science Publishers, 2012)
This chapter is an edited section derived from the PhD thesis by Dr. Theodora Issa under the title ‘Ethical mindsets, aesthetics and spirituality: A mixed-method approach analysis of the Australian Services Sector’ a winner of 2010 Outstanding Doctoral Research Award by Emerald/EFMD, under the category of Corporate Governance, sponsored by ‘Management Decision’. In 2009 a paper on this research under the title ‘Ethical Mindsets, spirituality and aesthetics in an Australian business context’ was awarded ‘The Best Paper Award’ at the 11th International Conference of Society For global Business and Economic Development.’ In August 2011, Dr. Theodora Issa was presented with the Curtin Business School’s ‘New Researcher of the Year 2010’ award.